2021
DOI: 10.1007/s43545-021-00254-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of digital technology in foreign language learning

Abstract: Digital technology has become an essential factor in the process of language learning. This quantitative study investigates the use of technology as well as teacher’s support in the process of technology-based learning of English as a foreign language (EFL) among high school students in Bosnia and Herzegovina. The data have been collected by the questionnaire modelling teachers' influence on learners' self-directed use of technology for language learning which consists of seven subscales. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Furthermore, some other researchers believe that online or blended learning has become more convenient, not only for the students but for the instructors as well, simply because of the new instructional practices that technology promotes and conducts only through online platforms and hence leaves the face‐to‐face way of teaching and learning behind due to its time and space constraints (Cigdem, 2015; Demiray, 2011). For example, innovative platforms such as Moodle, Blackboard, Claroline, and CanvasLMS have been established to make the online learning process more interesting and more interactive for the learners, which reciprocally leads to greater online engagement, e‐learning readiness, and positive attitudes toward LMS in the online or blended way of studying (Adnan & Anwar, 2020; Bećirović et al, 2021; Cigdem & Ozturk, 2016; Gherhes et al, 2021; Muthuprasad et al, 2021). However, Gherhes et al (2021) and Adnan and Anwar (2020) found a lack of the aforementioned practical applications in their studies and thus claimed that e‐learning was to be considered an alternative and not a norm for the time being.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some other researchers believe that online or blended learning has become more convenient, not only for the students but for the instructors as well, simply because of the new instructional practices that technology promotes and conducts only through online platforms and hence leaves the face‐to‐face way of teaching and learning behind due to its time and space constraints (Cigdem, 2015; Demiray, 2011). For example, innovative platforms such as Moodle, Blackboard, Claroline, and CanvasLMS have been established to make the online learning process more interesting and more interactive for the learners, which reciprocally leads to greater online engagement, e‐learning readiness, and positive attitudes toward LMS in the online or blended way of studying (Adnan & Anwar, 2020; Bećirović et al, 2021; Cigdem & Ozturk, 2016; Gherhes et al, 2021; Muthuprasad et al, 2021). However, Gherhes et al (2021) and Adnan and Anwar (2020) found a lack of the aforementioned practical applications in their studies and thus claimed that e‐learning was to be considered an alternative and not a norm for the time being.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, digital technology use in foreign language learning meets their unconscious expectations and "enables them to use the means and way how they normally search for information, communicate, exchange experiences and participate in events on a daily basis" (Troncarelli,118). It is thus not surprising that the current global research on learning English as a foreign language has shown that students mostly have a positive attitude towards ICT use in the learning process (e.g., Alsulami, 2016;Ayres, 2002, p. 247;Bećirović, Brdarević-Čeljo & Delić, 2021;Liu, 2009;Son, Park & Park, 2017). The results of the research conducted by Alsulami (2016, p. 13) on the attitudes of female students from Saudi Arabia (N=36) towards the impact of technology on learning English as a foreign language showed that 97.2% of participants enjoyed using technology in the English language learning, and that 94.7% of students preferred technology to use to improve their speaking, reading, writing and listening skills.…”
Section: Discussionmentioning
confidence: 99%
“…They expressed their readiness to learn more about digital technology as well as the opinion that it was important for them to improve their digital fluency and that their learning could be improved through the use of digital tools and resources (Son, Park & Park, 2017, p. 94). iv In their research conducted in Bosnia and Herzegovina, Bećirović et al (2021) analyzed the perceptions of secondary school students (N=173) about learning English via technology, and the correlation of their perceptions with their school success, gender and learning context. They also analyzed the perception and attitudes of students about teachers' support in this entire process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the rapid transfer of lessons into an online environment meant that a loss of teaching quality was often observed. Purposeful guidance through these new learning possibilities can, however, result in varied prospects of connecting individual needs to a great diversity of learning styles and methods (Bećirović et al, 2021).…”
Section: E-learningmentioning
confidence: 99%